Rules Of Getting Young Children Talk in the Untold Narrations: An Islamic Fiqh Educational Study - Ali, Enas Abdulrazzaq (International Journal of Psychosocial Rehabilitation, 2020)
Praise be to God, Lord of the worlds, and prayers and peace be upon our master Muhammad and upon his family and companions, My research this under the title (the provisions of interrogation of young people in what is hidden from the news of the house (an educational jurisprudence study)) in which a statement that interrogation is a type and form of espionage, and a statement of the rule of espionage and thus a statement of the rule of interrogation of young people, and I have studied this act in terms of jurisprudence and educational, Between the legal punishment for such an act in the world and in the brotherhood as well as the social harms of such actions, and I develop solutions in an attempt to find some solutions to get rid of it and not spread it in society, this is an educational Sharia study to address this phenomenon, as the Islamic religion legislated the privacy of the individual before more than four Ten centuries. And he recommended to the Muslim individual to protect the nakedness of his Muslim brother if he could. The Almighty arranged punishments in this life and intense promises in the Hereafter, to deter any violator of his orders. On the other hand, God made- the Almighty- the preservation of the privacy of the individual one of the characteristics of the believers, who believed God and His Messenger and worked in his law. And my research consisted of an introduction and several topics: I knew the relevant title and words. It showed the position of Sharia on interrogating the young. And touched on the consequences of interrogating the young. I explained some of the implications of interrogating the young. She addressed the reasons for the spread of the phenomenon of interrogation of young people and ways to reduce them, and put some recommendations in the conclusion, and among these recommendations first and most important: Return to God by repentance and his question, get rid of this disease, but it is the love of knowing the news of others and caring about this thing and make the effort to reach it. Second: Keeping the tongue out of the uttering of words and what is of no use in it. It has been said: “If you speak, remember God’s listening to you. Third: Not to interfere with the privacy and affairs of others, which clash with Islamic law and its texts. When we know the limits of the question and interfere in the affairs of others, our social life rises to high levels. Fourth: Following the example of the Prophet Muhammad, may God’s prayers and peace be upon him, and not transferring or transmitting private secrets. It was narrated from the Prophet, may God’s prayers and peace be upon him, from the hadith of Abdullah bin Masoud- may God be pleased with him- that he said- peace and blessings be upon him-: No one tells me anything, “I mean Something that must be thought bad about it, “I love to go out to you while I am a sound-minded (). What is the most beautiful religion of Islam, and it guides us to the best and most noble morals. Fifth: The constant preoccupation with good deeds with what is beneficial and beneficial.